Pain-related stigma as a social determinant of health in diverse pediatric pain populations - Wakefield, Emily O.; Kissi, Ama; Mulchan, Siddika S.; Nelson, Sarah; Martin, Sarah R. (Frontiers in Pain Research, 2022)
Pediatric patients with invisible symptomology, such as chronic pain syndromes, are more likely to experience pain-related stigma and associated discrimination by others, including medical providers, peers, school personnel, and family members. The degree of this pain-related stigma may depend on several social dimensions, including observer (e.g., attentional and implicit biases) and patient characteristics (e.g., racial identity, socioeconomic stressors). In this mini-review, we introduce the concept of pain-related stigma, and the intersectionality of stigma, within the context of social determinants of health in pediatric pain populations. Stigma theory, observer attentional biases, healthcare provider implicit/explicit biases, adverse childhood experience, and psychophysiology of socio-environmental stressors are integrated. Several ethical, clinical, and research implications are also discussed. Because the study of pain-related stigma in pediatric pain is in its infancy, the purpose of this conceptual review is to raise awareness of the nuances surrounding this social construct, propose avenues through which stigma may contribute to health inequities, present frameworks to advance the study of this topic, and identify areas for further investigation.